Legitimacy : the state and beyond - Sadurski, Wojciech, 1950-; Sevel, Michael; Walton, Kevin (Law teacher) (Oxford : Oxford University Press, 2019)
Traditionally, political legitimacy has been associated exclusively with states. But are states actually legitimate? And why should discussions of legitimacy focus only on the nation-state? This volume explores how legitimacy is intertwined with notions of statehood and how it reaches beyond the state into supranational institutions.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Legitimacy of governments; Political science -- Philosophy